Income Analysis of Micro and Small Enterprises (MSEs) During the Covid-19 Pandemic: Evidence from Indonesia - Rochmatullah, Mahameru Rosy; Jati, Ade Khurnia; Fauzan, F (Universitas Muhammadiyah Surakarta, 2022)
Micro and Small Enterprises (MSEs) are one of the economic sectors that have been severely affected by the Covid-19 pandemic. MSE actors experienced decreased income due to declined sales and marketing limitations caused by restrictions on working hours imposed by the government and reduction in workforce done by business owners to reduce spending and incompatible information technology capabilities for MSE buying and selling transactions. This study aims to analyze the capability of MSEs to earn income during the Covid-19 pandemic. To be more specific, this study focused on several factors that influence income, namely working hours, total workforce, education level, information technology, and government capital assistance. By employing multiple linear regression, the study results indicated that capital assistance from the government could explain the income gain of MSE actors. Meanwhile, the other four variables did not have any impact on MSE income.